Effect of neutron irradiation and doping level on defect structure formation in gallium arsenide crystals - Seitmuratov, M.S.; Klad'ko, V.P.; Gudymenko, O.I.; Datsenko, L.I.; Prokopenko, I.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
Using the technique of diffuse x-ray scattering at the "tails" of diffraction reflection curves, we analyze the effect of irradiation of dislocation GaAs crystals with high-energy neutrons on evolution of radiation clusters as a function of fluence and doping level. The effect of doping level on size of the above defects is shown to be considerable at low fluences. We advance a model for disordered regions in an irradiated crystal based on the results of x-ray experiments.